Transformasi Digital Pengawasan Pendidikan: Strategi Mengatasi Ketimpangan Rasio Pengawas Madrasah di Provinsi Jambi - Anwar (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article is motivated by a serious challenge in madrasah (Islamic school) supervision in Jambi Province: the extreme disparity in the supervisor-to-madrasah (Islamic school) ratio, which leads to ineffective supervision and widens the quality gap between regions. Data shows a sharp disparity, from the ideal ratio of 1:4.4 in Jambi City to an excessive workload of 1:25.5 in West Tanjung Jabung Regency, which reduces supervision to an administrative formality and compromises its pedagogical development function. Through USG analysis, the issue of "the absence of an integrated digital supervision system" was identified as a top priority due to its potential as a multiplier effect. This article uses the frameworks of Gap Theory, Systems Theory, and Agency Theory to dissect the root cause of the problem and review the concepts of e-supervision, decentralized supervision, and data-driven Continuing Professional Development (PPB). As a strategic solution, a policy is proposed to develop and implement an integrated digital-based supervision system (e-Supervision). This platform is designed to streamline processes, reduce administrative burdens, and provide real-time data for accountable decision-making. The implementation of e-supervision is expected to not only address geographic and resource constraints but also transform the role of supervisors into strategic facilitators. This policy also serves as a foundation for empowering madrasah principals as internal supervisors and fostering a culture of collaboration through the Professional Learning Community (PLC), creating a fair, accountable, and data-driven supervisory ecosystem for equitable improvement of madrasah education quality across Jambi Province.